Human umbilical veins and autogenous veins as canine arterial bypass grafts. - Oblath, R W (1978)
Glutaraldehyde treated human umbilical veins (Dardik Biograft) were used to bypass short segments of the femoral artery in 15 dogs and were compared to autogenous jugular veins placed in the contralateral femoral artery of each animal. All 15 autogenous jugular veins remained patent for the four month period of observation whereas thrombosis occurred in seven of 15 umbilical vein grafts. This patency rate of 53% was significantly lower than that observed for autogenous jugular veins (p less than 0.01). Neointimal Fibrous Hyperplasia (NFH) a the proximal anastomosis was responsible for six of the seven umbilical vein graft occlusions. Of the eight patent umbilical veins, five had varying degrees of proximal anastomotic stenosis secondary to NFH. Histological examination of each graft revealed significant fibroblastic proliferation and collagen deposition within the lumen of stenosed and thrombosed grafts. Although human umbilical veins have distinct advantages over other prosthetics, such as availability and flexibility, the incidence of experimental neointimal fibrous hyperplasia causing anastomotic stenosis and thrombosis is prohibitively high.